Organizational practices across cultures: An exploration in six cultural contexts - Fischer, Ronald; Ferreira, Maria Cristina; Asmar, Eveline Maria Leal; Baris, Gulfidan; Berberoglu, Gunes; Dalyan, Figen; Wong, Corbin C.; Hassan, Arif; Hanke, Katja; Boer, Diana (Sage, 2013)
This study examined organizational practices in a sample of 1239 employees from various organizations in Argentina, Brazil, Malaysia, New Zealand, Turkey, and the United States. Twenty-four items measuring employee-orientation, formalization, and innovation practices showed a clear factorial structure across all samples, along with good reliabilities. Significant organizational position differences were found for employee-orientation and innovation practices. Sector differences were found for formalization and innovation practices. Cultural differences were found for employee-orientation and innovation practices, which can be explained using macroeconomic indicators,tightness–looseness, and individualism. Our study demonstrates the importance of individual, organizational, economic, and cultural level for understanding perceptions of organizational practices across a wider range of societies.